Primary data on economic activity and water use in prototype oil shale development areas of Colorado; an initial inquiry - Gray, S. Lee (Sanford Lee), author; Environmental Resources Center, Colorado State University, publisher (Colorado State University. Libraries, 1974)
Potential impacts of oil shale development on the economies of certain Western Slope communities in Colorado are quite large. These impacts will likely exert a substantial pressure on the land and water resource lease of the area in addition to the effects upon community development, regional income, income distribution, and a changing mix of business activity. In order to approach future research on these issues this "seed" research effort was designed to (1) promote interaction and interchange of ideas among researchers and members of the affected communities, (2) to identify important areas of research needs in the oil shale region, and (3) to initialize the collection of primary data depicting the economic structure of the oi1 shale communities.
June 1974.
Keywords: Colorado -- Economic conditions; Oil-shale industry -- Colorado; Water-supply -- Colorado